X and Y-coordinates of Pell equation of some special forms - Zottor, Faith Shadow (My University, 2024)
This work primarily characterises the values of d in Pell equation X 2 −dY 2 = ±1 that have at least some specified number of the sequence of X or Y solutions belonging to some interesting sequence of positive integers.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Mathematics, University of the Witwatersrand, Johannesburg, 2023